2013
DOI: 10.1167/iovs.12-10725
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model of Limbal Stem Cell Deficiency Induced by Topical Medication With the Preservative Benzalkonium Chloride

Abstract: METHODS. BAC solutions (0%-0.5%) were applied to the mouse ocular surface for 4 weeks. Corneal neovascularization, inflammation, and epithelial status were observed under slit-lamp microscope. The eyeball and ocular surface tissues were collected at 4 and 12 weeks and labeled with a series of antibodies. Limbal structure was evaluated by light and transmission electron microscopy (TEM). Corneal impression cytology was performed at 12 weeks, and specimens were labeled with periodic acid Schiff (PAS) reagents.RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 33 publications
3
45
0
3
Order By: Relevance
“…They proposed that limbal epithelial thickness might be intended as a surrogate of the limbal stem cells status since it appears to directly correlate and represent the stem cell density. 32 To further support this hypothesis, Lin et al 33 reported that the instillation of BAK 0.5% four times per day for 4 weeks in a mouse model induced the typical manifestations of LSCD, including corneal neovascularization, severe inflammation in the stroma, and diffuse epithelial defect. The mechanisms leading to POV alterations in glaucoma were not previously considered and, therefore, are unknown; nevertheless, inflammatory processes occurring within limbal epithelium and diffusing for contiguity in depth finally reaching POV, may be hypothesized.…”
Section: Discussionmentioning
confidence: 98%
“…They proposed that limbal epithelial thickness might be intended as a surrogate of the limbal stem cells status since it appears to directly correlate and represent the stem cell density. 32 To further support this hypothesis, Lin et al 33 reported that the instillation of BAK 0.5% four times per day for 4 weeks in a mouse model induced the typical manifestations of LSCD, including corneal neovascularization, severe inflammation in the stroma, and diffuse epithelial defect. The mechanisms leading to POV alterations in glaucoma were not previously considered and, therefore, are unknown; nevertheless, inflammatory processes occurring within limbal epithelium and diffusing for contiguity in depth finally reaching POV, may be hypothesized.…”
Section: Discussionmentioning
confidence: 98%
“…Benzalkonium chloride (BAC) has been used to cause corneal surface damage to model dry eye disease in mice (Lin et al, 2011;He et al, 2012;Sarkar et al, 2012;Xiao et al, 2012Xiao et al, , 2013Lin et al, 2013;Zhang et al, 2014). The degree of corneal surface damage is proportional to the concentration and duration of BAC.…”
Section: Corneal Surface Damage Causes Light Aversionmentioning
confidence: 99%
“…Alkali substances are known to cause severe ocular damage and inflammation with compromising stroma and resulting in corneal ulceration, hyphema, hypopyon, and even corneal perforation (Ma et al, 2006). Other models involve surgical removal of the limbal tissue (Chen and Tseng, 1991), cauterization (Majo et al, 2008) and more recently, using benzalkonium chloride to simulate chronic injury to the ocular surface (Lin et al, 2013). In this study, our goal was to evaluate and validate a reproducible mouse model of LSCD using mechanical and thermal injury in a controlled manner, thereby avoiding extensive damage to the corneal stroma and other anterior chamber structures.…”
mentioning
confidence: 99%